PERUBAHAN IDENTITAS BUDAYA GENERASI MUDA SUKU ANAK DALAM DI ERA MODERNISASI KECAMATAN NALO TANTAN KABUPATEN MERANGIN - Dena Ramadani; Suci Rahmadhani; Basyarul Aziz (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study discusses the changes in cultural identity among the younger generation of the Anak Dalam Tribe in Nalo Tantan District, Merangin Regency. This study aims to determine the forms of cultural identity changes and the factors that influence these changes. This study uses a qualitative method with a descriptive approach. Data collection techniques were carried out through observation, interviews, and documentation. The results of the study indicate that there has been a change in cultural identity among the younger generation of the Anak Dalam Tribe, which is evident in their dress, language use, social patterns, and the decreasing involvement of the younger generation in traditional activities. These changes are influenced by developments in technology, education, social media, and social relations with outsiders. However, some young people still strive to maintain local culture and participate in traditional activities in the community. Based on the results of the study, it can be concluded that modernization has influenced the changes in the cultural identity of the younger generation of the Anak Dalam Tribe, so the role of families, traditional leaders, and the community is needed in maintaining local culture so that it can survive amidst the changing times.